Detection of Soil Water Content Using Continuous Wave Ground Penetrating Radar - Sonal Oimbe; Rahul Ingle; Raval Awale (Politeknik Negeri Padang, 2018)
In this work, continuous wave ground-penetrating radar (CW-GPR) has been used for detecting the soil water content in context to farm management. It is here speculated that CW-GPR utilized to observe variations in Soil parameters in different geographical area where traditional methods fails such as reflection-based GPR method. An experiment was performed on different farms in and around Mumbai city locality in a 20 * 14 m section of natural grassland at the SAMEER- IIT BOMBAY Research Facility in Mumbai city, INDIA. Two survey methods such as velocity analysis and GPR reflection surveys of ground wave were inefficient at the experiment site due to the signal attenuation which is related with the clay-rich soil. CW-GPR data sets were collected on regular and daily basis during a 5-d period in February 2017. The samples of soil were collected for analysis purpose from the mentioned geographical area. The clear response has been observed for early time signal amplitude to changes in soil water content using CW-GPR data. The strong correlation has been observed between the GPR data sets with Soil water content, which is uniform with the CW-GPR dependence on relative permittivity. The outcome reveals that the CW-GPR method can be utilized to acquire spatially distributed information on subsurface moisture content in clay-rich soils.